Enriched housing enhances recovery of limb placement ability and reduces aggrecan-containing perineuronal nets in the rat somatosensory cortex after experimental stroke. - Alexandre Madinier (Public Library of Science (PLoS), 2014)
Stroke causes life long disabilities where few therapeutic options are available. Using electrical and magnetic stimulation of the brain and physical rehabilitation, recovery of brain function can be enhanced even late after stroke. Animal models support this notion, and housing rodents in an enriched environment (EE) several days after experimental stroke stimulates lost brain function by multisensory mechanisms. We studied the dynamics of functional recovery of rats with a lesion to the fore and hind limb motor areas induced by photothrombosis (PT), and with subsequent housing in either standard (STD) or EE. In this model, skilled motor function is not significantly enhanced by enriched housing, while the speed of recovery of sensori-motor function substantially improves over the 9-week study period. In particular, this stroke lesion completely obliterates the fore and hind limb placing ability when visual and whisker guidance is prevented, a deficit that persists for up to 9 weeks of recovery, but that is markedly restored within 2 weeks by enriched housing. Enriched housing after stroke also leads to a significant loss of perineuronal net (PNN) immunoreactivity; detection of aggrecan protein backbone with AB1031 antibody was decreased by 13-22%, and labelling of a glycan moiety of aggrecan with Cat-315 antibody was reduced by 25-30% in the peri-infarct area and in the somatosensory cortex, respectively. The majority of these cells are parvalbumin/GABA inhibitory interneurons that are important in sensori-information processing. We conclude that damage to the fore and hind limb motor areas provides a model of loss of limb placing response without visual guidance, a deficit also seen in more than 50% of stroke patients. This loss is amenable to recovery induced by multiple sensory stimulation and correlates with a decrease in aggrecan-containing PNNs around inhibitory interneurons. Modulating the PNN structure after ischemic damage may provide new therapies enhancing tactile/proprioceptive function after stroke.